Differences in wings may be sufficient to separate the sexes and two species of Gynaikothrips Zimmermann (Thysanoptera: Phlaeothripidae)? - Santos, Priscila Paredes dos; Silva Junior, Juvenal Cordeiro; Nunes, Lorena Andrade (EntomoBrasilis, 2022)
In this study, we use geometric morphometry to discriminate thrips of the species Gynaikothrips uzeli (Zimmerman) and Gynaikothrips ficorum (Marchal) and also to detect sexual dimorphism in these species. Two hundred individuals, one hundred females and one hundred males, from G. uzeli and G. ficorum, were used to verify sexual dimorphism. For interspecific differentiation, two hundred females were used, one hundred individuals of each species. It was possible to observe differences in the shape of the wing between sexes in both species. In G. uzeli, the first two main components explain 92.5% of the total variation of individuals. The first main component explains 87% and the second 5.5 of the total variation of individuals. For G. ficorum, the first two main components explain 78.2% of the total variation of individuals. The first principal component contributed with 62% and the second principal component with 16.2% of the variation of the shape of the wing. Besides, significant interspecific differences were observed in the shape of the wing, where the first two main components were sufficient to explain 86% of the total variation of the individuals. The first principal component explained 76.2% and the second 9.8% of the total variation of the individuals, being possible to verify differences in the shape of the wing of these two species. Geometric morphometry is a viable technique for assessing sexual dimorphism, as well as interspecific differences in the shape of the wings of these species, which are morphologically very similar.